Use of lyophilised and powdered Gentiana lutea root in fresh beef patties stored under different atmospheres - Nurul Aini, Mohd Azman; Gordon, Michael H.; Skowyra, Monika; Segovia, Francisco; Almajano, María Pilar (Wiley Online Library, 2015)
Gentiana lutea root is a medicinal herb that contains many active compounds which contribute to physiological effects, and it has recently attracted much attention as a natural source of antioxidants. The aim of this study was to evaluate the effects on the colour, pH, microbial activities, sensory quality and resistance to lipid oxidation (through the thiobarbituric acid method) during storage of beef patties containing different concentrations of G. lutea. Fresh beef patties were formulated with 0–5 g kg−1 of G. lutea and 0 or 0.5 g kg−1 of ascorbic acid and packed in two different atmospheres, Modified Atmosphere 1 (MAP1) and Modified Atmosphere 2 (MAP2), and stored at 4 ± 1 °C for 10 days. MAP1 contained 20:80 (v/v) O2:CO2 and MAP2 contained 80:20 (v/v) O2:CO2.